Nephrotic syndrome and thymoma recurrence: a case report - Vilela, Sara; Sousa, Mariana; Cruz, Gonçalo; Pereira, Fernando; Bravo, Pedro (Brazilian Journal of Case Reports, 2022)
Paraneoplastic syndromes, such as myasthenia gravis, pure red-cell aplasia and systemic lupus erythematosus are well-documented in thymoma. Association with glomerulopathies is rare and may occur several years after thymectomy. We report a case of a 60-year-old male presenting with nephrotic syndrome after thymectomy due to thymoma. The kidney biopsy showed minimal change disease. The patient went into complete remission after treatment with corticosteroids. The pathogenesis of glomerular lesions associated with thymic disease remains controversial.